The doctrine of reconciliation ; part 2 - Barth, Karl, 1886-1968; Torrance, Thomas Forsyth, 1913-; Bromiley, Geoffrey William (Edinburgh, Scotland T and T Clark, 1961)
Includes bibliographical references
Original German ed. : Die Kirchliche Dogmatik, IV : Die Lehre von der Versohnung, 2.
Keywords: Jesus Christ -- person and offices; Theology